Holocene Nile dynamics shaped the physical and cultural landscape of ancient Nubia - Jan Peeters; Timotheus G. Winkels; Pawel Wolf; Tim B. B. Skuldbøl; Elizabeth L. Chamberlain; Saskia Büchner-Matthews; Sami M. Elamin; El-Hassan A. Mohamed; Geoff Emberling (Proceedings of the National Academy of Sciences, 2026)
The Nile River played a central role in ancient civilizations of Northeast Africa, yet its response to Holocene climate change and its impact on societies along its course remain poorly understood. Here we show how climatic and environmental changes over the past 12,500 y shaped the riverine landscape below the Nile’s Fourth Cataract and affected the Nubian empire of Kush in northern Sudan. Using 26 sediment cores dated by optically stimulated luminescence and radiocarbon, with additional chronological constraints from pottery typology, we reconstruct the evolution of the Nile near Napata, the major urban center of ancient Kush at Jebel Barkal (near present-day Karima). Napata, renowned for its pyramids, temples, and palaces, flourished from about 1070 BCE to 350 CE and is now a UNESCO World Heritage site. Our results reveal that the Early–Middle Holocene Nile deeply incised its valley, followed by widespread floodplain buildup around 4,000 y ago as rainfall and river flow patterns changed. During the Late Holocene, the Nile River near Jebel Barkal remained remarkably stable, due to its narrow valley with constrained outflow and enhanced sediment deposition from upstream energy dissipation at the cataract. This long-term stability promoted fertile floodplain development and, together with the sacred prominence of Jebel Barkal, fostered enduring settlement and ritual activity. These findings demonstrate how hydroclimatic change, geomorphic stability, and cultural adaptation were intertwined in shaping the environmental foundation of ancient Nubia.